ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ( STUDI PADA UD. KARYA MANDIRI LODOYO KAB. BLITAR) - Erisxy Pebriana Via Nanda; Tanto Askriyandoko Putro (Ma Chung Press, 2022)
This study aims to determine the effect of price and product quality on consumer purchasing decisions UD. Karya Mandiri of Lodoyo, Blitar Regency. In this study, a descriptive-quantitative approach was used. The research instrument used and the data analysis are quantitative. Data collection was carried out by means of observation and field studies. The population in this study are existing consumers with a total of 40 respondents consisting of 20 regular consumers and novice consumers. The sample of this study used the population. Data analysis methods used in this study include; validity test, reliability test and multiple linear regression analysis with t test, F test and coefficient of determination . Simultaneously, the results in this study there are consumer purchasing decisions UD. Karya Mandiri of Lodoyo, Blitar Regency. with a calculated F value of 8.902 with a sig of 0,002b. The results of this study also prove that there is an influence between price and product quality on the purchasing decisions of UD. Karya Mandiri of Lodoyo, Blitar Regency. The conclusion of this study is that both price and product quality variables have an influence on buyer decisions.